Cosmic parallax: possibility of detecting anisotropic expansion of the universe by very accurate astrometry measurements - Quercellini, Claudia; Quartin, Miguel; Amendola, Luca (Arxiv, 2009)
Refined astrometry measurements allow us to detect large-scale deviations from isotropy through real-time observations of changes in the angular separation between sources at cosmic distances. This "cosmic parallax" effect is a powerful consistency test of FRW metric and may set independent constraints on cosmic anisotropy. We apply this novel general test to LTB cosmologies with off-center observers and show that future satellite missions such as Gaia might achieve accuracies that would put limits on the off-center distance which are competitive with CMB dipole constraints.